MODERN UNIVERSITY PUBLISHING FUTURE: GUIDELINES FOR PERSPECTIVE - GALINIENĖ, GINTARĖ (Knygotyra, 2010)
The changing role of the modern university, emergence of a new high school’s mission, imposing new forms of science communication expand the traditional publishing opportunities on the university level. It is noted that the University of Publishers have made considerable progress in helping to publish scientific journals, especially in the digital space. However, the trend appears that the printed form of scientific journals gradually disappears. It is possible to hypothesize that the next digital publishing university level would be establishment of new publishing formats which enable the application of a digital technology which will allow scientists to carry out a built-in digital research, rapidly disseminate it and discuss with other researchers, and dynamically update their content by using the possibilities offered by the new generation of the web. However, most research in the future will be mainly disseminated and published in scientific digital communication channels. Thus, as prospective modern university publishing guidelines for the future, there are four problems to be treated: changes in the science communication paradigm; double scientific publishing in the form of àà“paper-digital journal”; scientific journals on the Internet; reviewing the matter. Thus, the university also needs to develop its new business vision – to become an open space for researchers to share their ideas and disseminate a range of scientific ideas that would find response in other scientists or scientific communities, reasoned criticism, comment or approval, all of which encourage individual or general academic research development. Online access to scientific production and its digital form opens up new opportunities for the academic development of the idea of unlimited scope for research, stimulates discussion with other researchers, sharing their research, opportunities to correct errors, submit their comments, indicate errors, or to contribute to the scientific content of a paper by adding new insights. The final transformation of the peer review model would produce tangible results.